Phase boundary between Na–Si clathrates of structures I and II at high pressures and high temperatures - Jouini, Z.; Kurakevych, O.O.; Moutaabbid, H.; Godec, Le Y.; Mezouar, M.; Guignot, N. (Сверхтвердые материалы, 2016)
Understanding of the covalent clathrate formation is a crucial point for the design of new superhard materials with intrinsic coupling of superhardness and metallic conductivity. It has been found that silicon clathrates have the archetype structures, which can serve an existent model compounds for superhard clathrate frameworks Si–B, Si–C, B–C and C with intercalated atoms (e.g., alkali metals or even halogens) that can assure the metallic properties. Here we report our in situ and ex situ studies of high-pressure formation and stability of clathrates Na₈Si₄₆ (structure I) and Na₂₄₊xSi₁₃₆ (structure II). Experiments have been performed using standard Paris–Edinburgh cells (opposite anvils) up to 6 GPa and 1500 K. We have established that chemical interactions in the Na–Si system and transition between two structures of clathrates occur at temperatures below silicon melting. The strong sensitivity of crystallization products to the sodium concentration has been observed. A tentative diagram of clathrate transformations has been proposed. At least up to ~ 6 GPa, Na₂₄₊xSi₁₃₆ (structure II) is stable at lower temperatures as compared to Na₈Si₄₆ (structure I). Изучен in situ и ex situ процесс образования при высоких давлениях и стабильности клатратов Na₈Si₄₆ (структура I) и Na₂₄₊xSi₁₃₆ (структура II). Эксперименты были проведены в стандартных Париж-Эдинбургских ячейках (opposite anvils) при давлениях и температурах до 6 ГПа и 1500 K соответственно. Установлено, что химическое взаимодействие в системе Na–Si и переходы между двумя структурами клатратов происходят при температурах ниже температуры плавления кремния. Предложено первое приближение диаграммы превращений клатратов. Отмечена большая чувствительность продуктов кристаллизации к концентрации натрия. Na₂₄₊xSi₁₃₆ (структура II) является стабильной при более низких температурах по сравнению с Na₈Si₄₆ (структура I), по крайней мере до ~ 6 ГПа. Вивчено in situ і ex situ процес утворення при високих тисках і стабільності клатратів Na₈Si₄₆ (структура I) і Na₂₄₊xSi₁₃₆ (структура II). Експерименти було проведено в стандартних Париж-Единбурзький комірках (opposite anvils) при тисках і температурах до 6 ГПа і 1500 K відповідно. Встановлено, що хімічна взаємодія в системі Na–Si і переходи між двома структурами клатратов відбуваються при температурах нижче температури плавлення кремнію. Запропоновано перше наближення діаграми перетворень клатратів. Відзначено велику чутливість продуктів кристалізації до концентрації натрію. Na₂₄₊xSi₁₃₆ (структура II) є стабільною при більш низьких температурах у порівнянні з Na₈Si₄₆ (структура I), принаймні до ~ 6 ГПа.